The handbook of global climate and environment policy (Hoboken, NJ John Wiley & Sons Inc, 2013)
The Handbook of Global Climate and Environment Policy presents an authoritative and comprehensive overview of global policy on climate and the environment. It combines the strengths of an interdisciplinary team of experts from around the world to explore current debates and the latest thinking in the search for global environmental solutions. Explores the environmental challenges we currently face, and the concepts and approaches to solving these Questions the role of global actors, institutions and processes, and considers the links between global climate and environment policy, and that of the global economyHighlights the connections between social science research and global policy Brings together authoritative coverage of recent research by internationally?renowned experts from around the world, including from North America, Europe, and Asia Provides an essential resource guide for students and researchers from across a wide range of related disciplines ? from politics and international relations, to environmental sciences and sociology ? and for global policy practitioners
Includes bibliographical references and index.
Keywords: Climatic changes -Government policy